Cyber Security and Legal Protection for Dropshipping Transactions in Indonesia: between State Law and Islamic Law - Khairudin Khairudin; Yusuf Baihaqi; Abdul Qodir Zaelani; Luqman Hafiz; Enizar Enizar; Muhammad Reza Fahlevy (JURIS (Jurnal Ilmiah Syariah), 2024)
This study aims to explain the cybersecurity and legal protection of dropshipping transactions from the Indonesian and Islamic economic law perspective. The normative and comparative judicial approaches were applied to achieve the research objectives. Descriptive and prospective analysis methods are used, and data are collected through primary and secondary sources. The findings revealed that despite the continuous growth of dropshipping contracts, Indonesia has no direct laws and regulations that particularly deal with the dropshipping mechanism and provide this cyber security to the system. In Islam, the dropshipping mechanism is linked with three types of contracts: Salam, Samsarah, and Wakalah. However, each type carries certain limitations as per Islamic/Sharia principles. Simultaneously, along with the cyber security laws available in financial transactions, the Islamic Fatwa can be regarded as a guide for dealing with dropshipping agreements and preventing cyber security. Furthermore, considering the increasing trend of dropshipping businesses, which is beneficial for the economic system, the existing cybersecurity laws and regulations must be amended to explicitly cover drop-shipping mechanisms.